Effect of Hydrolyzed Lima Bean Protein on the Quality of Low - Fat Ice Cream Products - Huu Khang Nguyen; Hoan Pham-Thi (Journal of Technical Education Science, 2025)
In this study, the possibility of replacing skim milk powder with hydrolyzed lima bean (Phaseolus lunatus L.) protein by alcalase (APPC) in low-fat ice cream formulations was evaluated at replacement levels of 0, 6, 12, 18, 24 and 30%. Increasing APPC substitution resulted in higher protein content (3.96–4.81%) and reduced carbohydrate (25.21–22.94%) and fat (2.20–1.72%) levels. APPC addition positively affected the physical properties by enhancing overrun and melting resistance while decreasing hardness. Sensory evaluations showed that substitutions between 6% and 18% did not significantly affect the ice cream’s sensory attributes, whereas higher substitutions (24–30%) introduced mild bitterness and reduced sensory quality. Moreover, substituting skimmed milk powder with APPC improved ice cream stability by decreasing bubble size and promoting even air distribution. The 18% APPC substitution provided the best balance of nutritional and sensory properties, indicating that APPC is suitable for large-scale low-fat ice cream production and can contribute to product diversification in the market.